Evolutionary patterns and development prospects for e-government: a Delphi-based approach to perceptions of the administrative agent - Ferreira, Fernando A. F.; Marques, Carla S. E.; Reis, Melanie M.; Ferreira, Neuza C. M. Q. F.; Çipi, Amali (Journal of Business Economics and Management, 2014)
Information technology is an open door for governments to service citizens in a more timely, cost-efficient and effective manner. Even considering citizen resistance, cultural adversity or changes in the economic agents’ relationship, few would contest that concern over the state of electronic government (e-government) has increased over the years. This concern has been responsible for the emergence of a wide range of new initiatives devoted to development of the information and knowledge society, which occupies a central place in government policies and planning strategies worldwide. In this paper, we aim to analyze the evolutionary patterns of e-government in Portugal and, based on an application of the Delphi technique, provide development prospects considering the perceptions of a panel of administrative agents. Despite the low use of e-government services, our study demonstrates that the administrative agent expresses overall satisfaction with its use. Additionally, the high level of modernization allows us to forecast the increased use of information and communication technologies in terms of e-government services.